Implementation of the Principle of Legal Certainty in the Making of Marriage Agreement Deeds by Notaries - Nugroho, Raditya Rizki; Wahyudi, Trubus (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze: 1) The implementation of the principle of legal certainty in the making of a marriage agreement deed by a Notary aims to provide legal guarantees for the husband and wife and third parties. This agreement must be made in the form of a notarial deed before the marriage takes place in order to have binding legal force. The Notary's role is to ensure that the agreement is in accordance with the provisions of the law, does not cause ambiguity, and is registered at the Civil Registry Office in order to strengthen legal protection. In addition to guaranteeing the rights and obligations of the couple, the application of the principle of legal certainty also prevents potential disputes and ensures transparency in the management of marital assets. Thus, the existence of a marriage agreement deed contributes to justice, legal security, and order in the marriage legal system in Indonesia. marriage in Indonesia. 2) The legal consequences of the application of the principle of legal certainty in the making of a marriage agreement deed by a Notary are that with the existence of a marriage agreement made in the form of an authentic deed and officially registered, legal certainty regarding ownership and management of assets in the marriage can be guaranteed. The Notary plays an important role in ensuring that the agreement is made in accordance with applicable legal provisions, so that it has binding legal force and can be used as valid evidence in the judicial process. In addition, the application of the principle of legal certainty in a marriage agreement also functions as preventive and repressive legal protection. Preventively, this agreement helps prevent potential disputes regarding property in marriage, while repressively, this agreement provides a strong legal basis for resolving conflicts in court if violations or disputes occur.Keywords: Marriage Agreement Deed; Notary; Principle of Legal Certainty.